1993
DOI: 10.1037/0021-9010.78.4.611
|View full text |Cite
|
Sign up to set email alerts
|

Generality and specificity in health behavior: Application to warning-label and social influence expectancies.

Abstract: The authors outlined a meta-theoretical and an analytic framework for construing the predictive effects of health-behavior expectancies, or beliefs, in terms of both general and specific processes. This framework was applied empirically to the investigation of the predictive effects of outcome expectancies related to the recently mandated alcohol-warning label as well as to expectancies reflecting social influence processes. Results showed that general and specific predictive effects of expectancies on alcohol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 58 publications
3
20
0
Order By: Relevance
“…One similarity across both samples is the highly significant positive effect of expected disinhibition in predicting alcohol use, as compared with the minimal effects of the negative expectancies measured by the flushing, physical impairment, and depression scales. A recent study by Stacy et al 34 confirms the salience of disinhibition as a distinct positive expectancy that is significantly predictive of alcohol use behaviors and probably most accessible to memory in the decision to drink or not drink alcohol.…”
Section: Discussionmentioning
confidence: 90%
“…One similarity across both samples is the highly significant positive effect of expected disinhibition in predicting alcohol use, as compared with the minimal effects of the negative expectancies measured by the flushing, physical impairment, and depression scales. A recent study by Stacy et al 34 confirms the salience of disinhibition as a distinct positive expectancy that is significantly predictive of alcohol use behaviors and probably most accessible to memory in the decision to drink or not drink alcohol.…”
Section: Discussionmentioning
confidence: 90%
“…The premise behind this study was that alcohol warning labels contain messages about negative outcomes associated with alcohol use, and hence the aim was to examine whether expectancies of such negative outcomes associated with alcohol use impact upon alcohol consumption and drink‐driving behaviours. The authors reported that both positive and negative alcohol‐related outcome expectancies predicted alcohol use and drink‐driving within the adolescent sample 22 . However, in their study examining the longer‐term effect of alcohol warning labels, MacKinnon and colleagues 19 reported the introduction of alcohol warning labels had no impact on outcome expectancies in their adolescent sample.…”
Section: Resultsmentioning
confidence: 97%
“…Outcome expectancies refer to an individual's estimation that a given behaviour will lead to a particular outcome 21 . One study identified for this review examined whether outcome expectancies have an impact on alcohol‐related behaviour 22 . The premise behind this study was that alcohol warning labels contain messages about negative outcomes associated with alcohol use, and hence the aim was to examine whether expectancies of such negative outcomes associated with alcohol use impact upon alcohol consumption and drink‐driving behaviours.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations